1998
DOI: 10.1084/jem.187.12.2045
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Mast Cells Determine Susceptibility to Ultraviolet B–induced Systemic Suppression of Contact Hypersensitivity Responses in Mice

Abstract: Different strains of mice have varying susceptibilities to ultraviolet radiation (UV) of wavelength 280–320 nm (UVB) for 50% suppression of systemic contact hypersensitivity (CHS) responses. Prevalence of histamine-staining dermal mast cells in different strains of mice (C57BL/ 6J, DBA/2, BALB/c) correlated directly with their susceptibility to UVB-induced systemic immunosuppression. BALB/c mice carrying Uvs1, a major locus for susceptibility to UV-induced immunosuppression, contained greater numbers of dermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
247
4
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(265 citation statements)
references
References 33 publications
8
247
4
2
Order By: Relevance
“…Whether cis-UCA binding to 5-HT 2A receptors expressed on T and B cells is responsible for IL-10 production remains to be seen. It is also well known that mast cell activation is critical for UV-and͞or cis-UCA-induced immune suppression (30,31). Kahlil et al (41) report that cis-UCA does not directly cause degranulation of mast cells, but rather stimulates neuropeptide release from peripheral nerves, which in turn activates mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether cis-UCA binding to 5-HT 2A receptors expressed on T and B cells is responsible for IL-10 production remains to be seen. It is also well known that mast cell activation is critical for UV-and͞or cis-UCA-induced immune suppression (30,31). Kahlil et al (41) report that cis-UCA does not directly cause degranulation of mast cells, but rather stimulates neuropeptide release from peripheral nerves, which in turn activates mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, serotonin͞ cis-UCA͞UV exposure was given 5 days before immunization and 15 days before challenge. We propose that serotonin or cis-UCA given well before challenge activates processes known to be critical for UV-and cis-UCA-induced immunosuppression, such as mast cell activation (30,31) and the secretion of antiinflammatory cytokines (14) that normally serve to dampen hypersensitivity reactions. UV exposure maybe acting in vivo to accelerate these normal feedback mechanisms, thereby promoting immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells represent potential sources of many mediators that can enhance or suppress the development, survival, proliferation, migration, maturation, or function of immune cells (reviewed in REFS [1][2][3][5][6][7][8]13,[16][17][18]21,30,31,43,44,[46][47][48][49][50][51][52][53][54][55][56]. Some individual mediators, such as histamine, can have both positive and negative immunomodulatory effects.…”
Section: Mast-cell Immunomodulatory Functions Immunomodulatory Activimentioning
confidence: 99%
“…Hart et al 49 showed that the ability of ultraviolet B (UVB) irradiation of the skin to induce systemic immunosuppression of contact hypersensitivity (CHS) responses to the hapten 2,4,6-trinitrochlorobenzene was markedly reduced in (C57BL/6 × DBA/2)F1-Kit W-f/W-f mice but was restored following mast-cell knockin. Several lines of evidence suggested that histamine was a major mediator of this UVBinduced, mast cell-dependent effect.…”
Section: Negative Immunomodulatory Functions In Vivomentioning
confidence: 99%
See 1 more Smart Citation